Increasing Village Economic Independence through Assistance in Traditional Herb Product Innovation - Tianjuan Xia; Haili Wang (Community Service Akseprin Journal, 2023)
Increasing village economic independence through assistance in traditional herb product innovation is carried out with the village community. This activity is a National Movement of Mental Revolution with the scope of activities of the Independent Movement. Assistance in packaging workshops for souvenirs, workshop and promotion assistance, tree planting activities and meetings for the preparation of outputs and final reports. The method implemented is to record citizens who will participate in this activity, and provide explanations related to the National Movement of Mental Revolution program with the community. Assisting packaging workshops for souvenirs related to product packaging and product branding so that they can be marketed and used as distinctive souvenirs. Carrying out business formation and promotion workshop assistance , aimed at increasing the promotion of village product innovation. Carrying out tree planting activities, the tree seeds planted are a composition of traditional herbs. The expected output of this activity is that the economy of the village community continues to grow by continuing to innovate through herbal products